Diagnostic Accuracy of CT Scan for Detecting Ongoing Internal Bleeding Following Torso Injury Keeping per Operative Findings as Gold Standard - Zafar, Ibtesam; Majeed, Ayesha Isani; Bhutta, Muzammil Rasheed; Khan, Amir; Khan, Muhammad Nasir Naeem; Siddiqui, Ayesha Shamim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of a CT scan for detecting ongoing internal bleeding following torso injury, keeping operative findings as the gold standard.Study Design: Cross-sectional validation study.Place and Duration of Study: Radiology Department, Pakistan Institute of Medical Sciences, Islamabad Pakistan, from Jul 2021 to Oct 2021.Methodology: Contrast-enhanced CT was carried out for 100 patients with torso injury to detect the incidence of extravasated contrast material, an outcome that signifies any active haemorrhages present. The findings were then compared with the peroperative findings of the patient.Results: We detected active haemorrhages in 48 out of 100 patients on Computed Tomography. A total of 83 injury sites were recorded. Active haemorrhages were mostly visible through the spill of contrast agents in a jet stream in 61(73.4%) out of 83 injury sites. Immediate surgical intervention was performed on all the patients who were detected with active haemorrhages on CT, which confirmed the findings. In 3 patients out of 100, CT did not detect active haemorrhage, but surgical intervention showed active haemorrhage on intra-peritoneal sites. Computed Tomography had a high diagnostic accuracy for torso injuries (97.0 %) with a sensitivity of 94. 11 % and a specificity of 100 %.Conclusion: Instantaneous surgical intervention is obligatory whenever contrast extravasation is identified on Computed Tomography (CT).